2016
DOI: 10.1016/j.mrfmmm.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase specific error rates and profiles identified by single molecule sequencing

Abstract: DNA polymerases have an innate error rate which is polymerase and DNA context specific. Historically the mutational rate and profiles have been measured using a variety of methods, each with their own technical limitations. Here we used the unique properties of single molecule sequencing to evaluate the mutational rate and profiles of six DNA polymerases at the sequence level. In addition to accurately determining mutations in double strands, single molecule sequencing also captures direction specific transver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 37 publications
3
48
0
Order By: Relevance
“…Hestand et al . measured the fidelity of Taq polymerase to be 4.4 × 10 −5 errors/base/cycle, and when normalized for the number of PCR cycles, our Taq measurements of 5.7 × 10 −5 sub/base/cycle are similar [15]. Phusion DNA polymerase (1.3 × 10 −6 sub/base/cycle in this study) was found to have a similar error rate by single-molecule sequencing (1.8 × 10 −6 sub/base/cycle) [15], but a lower error rate by another Illumina-based method (4.5 × 10 −7 total errors/base/cycle) [5], indicating there may be some discrepancy in the literature regarding the error rate of Phusion DNA polymerase.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Hestand et al . measured the fidelity of Taq polymerase to be 4.4 × 10 −5 errors/base/cycle, and when normalized for the number of PCR cycles, our Taq measurements of 5.7 × 10 −5 sub/base/cycle are similar [15]. Phusion DNA polymerase (1.3 × 10 −6 sub/base/cycle in this study) was found to have a similar error rate by single-molecule sequencing (1.8 × 10 −6 sub/base/cycle) [15], but a lower error rate by another Illumina-based method (4.5 × 10 −7 total errors/base/cycle) [5], indicating there may be some discrepancy in the literature regarding the error rate of Phusion DNA polymerase.…”
Section: Discussionmentioning
confidence: 93%
“…DNA polymerase replication fidelity has been extensively studied with multiple methods and various assay conditions. Assays to determine replication fidelity have utilized various approaches: blue/white screening ([7], [8], [9], and reviewed in [10]), forward mutation [11], denaturing gradient gel electrophoresis [12, 13], high throughput Sanger sequencing [14], or next-generation sequencing [5, 15, 16]. Differences in assay methodology, reaction conditions, template sequences and error reporting units can yield different absolute values for error rates.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations